2009
DOI: 10.1002/ajmg.b.31005
|View full text |Cite
|
Sign up to set email alerts
|

Suggestive evidence for linkage of ADHD features in bipolar disorder to chromosome 10p14

Abstract: Higher rates of bipolar disorder amongst the first-degree relatives of probands with ADHD, and increased rates of ADHD in the relatives of bipolar probands have been reported in many studies. This suggests some commonality in the genetic basis for bipolar disorder and ADHD. We hypothesized that ADHD symptoms in bipolar disorder may access a quantitative subphenotype that is genetically less complex and therefore advantageous for mapping studies. The Wender Utah Rating Scale (WURS) was used to quantify ADHD fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 45 publications
4
19
0
Order By: Relevance
“…The results also show that the reduction of symptoms in the case group was greater than that of the control group. Several similar studies have been conducted and it has been shown that micronutrients such as magnesium and zinc are associated with the treatment of ADHD symptoms (23)(24)(25)(26)(27)(28). Most of these studies have focused on zinc and are consistent with the findings of our study.…”
Section: Discussionsupporting
confidence: 91%
“…The results also show that the reduction of symptoms in the case group was greater than that of the control group. Several similar studies have been conducted and it has been shown that micronutrients such as magnesium and zinc are associated with the treatment of ADHD symptoms (23)(24)(25)(26)(27)(28). Most of these studies have focused on zinc and are consistent with the findings of our study.…”
Section: Discussionsupporting
confidence: 91%
“…According to the loading pattern, the three factors were tentatively named as follows: 'impulsivity and defiant behavior', first factor (IMP); 'inattention', second factor (INATT); and 'mood instability and anxiety', third factor (MOOD). It is important to note that these factors are compatible with similar factor analyses carried out in other studies (Caci et al, 2009;Joo et al, 2010). The mean values of each factor score for male and female participants were then compared.…”
Section: -Item Wender Utah Rating Scale Factor Extraction and Compasupporting
confidence: 63%
“…However, an alternative explanation is that the WURS-25 total score and each specific factor score reflect different genetic effects. In a linkage study with bipolar families, a stronger signal with the inattention factor was found in a different region (10p14, LOD = 3.35), although a linkage signal with the WURS-25 total score was found in the 12q24 region (LOD =2.05; Joo et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…We previously used the Wender Utah Rating Scale (WURS) to retrospectively measure the severity of childhood ADHD symptoms in BD and identified three heritable factors: impulsivity and defiant behavior, mood instability and anxiety, and inattention (Joo et al, 2009). Linkage analysis of the WURS measures in 57 BD families found modest evidence for linkage of the inattention factor to chromosome 5p15.3 near the dopamine transporter gene ( SLC6A3, DAT1 ) with a LOD score of 1.33 (Joo et al, 2009), where we have previously reported evidence for linkage of BD (Kelsoe et al, 1996; Kelsoe et al, 2001).…”
Section: Introductionmentioning
confidence: 99%